Assessing the trend of ozone concentration and its key influences at a monitoring station in Hanoi, Vietnam, in 2018–2020 - Ly, Bich Thuy; Vo, Le Ha; Cao, Mai Huong; Nguyen, Van Linh (Hue University Journal of Science: Natural Science, 2025)
Ozone (O3) is an air pollutant problem in Hanoi, indicating photochemical smog and posing health risks. The current O3 problem remains relatively underexplored. This study aims to evaluate the temporal trend of O3 formation over the period from 2018 to 2020 at a monitoring station in Hanoi and the relationship among O3 levels, the precursor, and meteorological factors. Multiple linear regression (MLR) and Boosted regression trees (BRTs) models were applied to analyse and quantify the influence of meteorological factors and precursor pollutants on O3 concentrations. The de-weather package was used to estimate O3 concentration after removing the meteorological effects. The monthly O3 concentration decreased in the winter season and rose in the summer season. The peak of hourly O3 levels was consistently observed between 12:00 and 15:00 across all seasons, corresponding to peak photochemical activity. Both MLR and BRTs show that temperature and solar radiation were the dominant drivers of O3 variability. Results from the BRTs model indicate that the de-weathering O3 concentrations exhibited much less variation than the observed values.